Unveiling the hidden link: fungi and HPV in cervical lesions - Zhang, Yulong; Chen, Lingsi; Li, Haibo; Zhuang, Yiling; Xie, Qing; Li, Wenwen; Yang, Xia; Zheng, Xiangqin; Suyu, Li; Yi, Huan (Frontiers in Microbiology, 2024)
Cervical cancer, ranks as the second most common cancer globally. Understanding combined infections' role, including Cervical fungi, is crucial in cervical carcinogenesis. This study aims to explore the potential correlation between HR-HPV, cervical fungi, and cervical cancer, while adjusting for various factors.Clinical data including age, gravidity, HPV (Human Papillomavirus) genotypes, cervical pathology, and p16/Ki67 expression were extracted. 5,528 participants were included in this study. Statistical analyses investigated associations between HPV/fungi co-infection and cervical lesions, employing multinomial logistic regression and interaction analysis. Results: Co-infection with fungi and HPV, compared with HPV infection alone, the risk of low-grade squamous intraepithelial lesions (LSIL) was reduced by 27% (OR=0.73, 95% CI: 0.59-0.90), the risk of high-grade squamous intraepithelial lesions (HSIL) was reduced by 35% (OR=0.65, 95% CI: 0.51-0.82), and the risk of cervical cancer was reduced by 43% (OR=0.57, 95% CI: 0.35-0.92). The interaction analysis revealed a negative interaction between fungal and HPV infections in the development of cervical cancer (RERI=-6.25, AP=-0.79, SI=0.52), HSIL (RERI=-19.15, AP=-0.37, SI=0.72) and LSIL (RERI=-1.87, AP=-0.33, SI=0.71), suggesting a sub-additive effect, where the combined effect of the two infections was less than the sum of their individual effects. In exploring the potential mechanism, we found that the co-infection group had significantly lower p16 positivity (54.6%) compared to the HPV-only group (60.2%) (p=0.004), while there was no statistically significant difference in Ki67 positivity.This study unveils the intricate relationship between cervical fungi and HPV in cervical lesions. Co-infection with fungi and HPV against cervical lesions compared to HPV infection alone, indicating a novel clinical interaction. Lower p16 positivity in co-infection hints at a protective mechanism, urging further exploration. and 30% of CIN III cases, are self-contained 4-6 , and the immune system typically clears HPV infections within two years 7 . Prolonged HPV presence, influenced by factors such as cervicitis or multiple sexual partners, results in a sustained high viral load 8 , contributing to cervical lesions and their severity 9,10 . Vaccines are an effective means of preventing HPV infection and reducing the risk of cervical lesions. Three commercial vaccines are available: